(untitled) (Economic and Political Thought, 2020)
The purpose of the article is to identify the situation of workers and identify factors that affected the situation in the labour market in Poland in 2009–2018. The research hypothesis is that the situation in the labour market in Poland was improving. Research questions, however, are whether and how the situation of workers, employees, and labour costs per employee and hour worked changed. The report also assesses the information on unemployment, including newly registered and deregistered unemployed, the unemployment rate and job offers. Based on these data, an analysis of changes in the level and calculated dynamics of growth is carried out. The statistical data of the labour market of the Central Statistical Office in Warsaw, published in the Statistical Yearbooks of the Republic of Poland for the years 2009–2018, are used for the analysis and evaluation. The years 2009–2018 are adopted for the analysis, because this is an important period for Poland as it covers the economic development, the economic crisis and the period after the crisis.